Improving Studentsâ Reading Comprehension Through Mind Mapping - Cahyani, Riska Dwi (JoLLIET, 2015)
The objectives of this research are: (1) to identify whether or not and to what extent the use of Mind Mapping improves the reading comprehension; and (2) to describe the class situation when Mind Mapping is implemented in the reading class of the seventh year students of SMP N 3 Colomadu. The problems faced by the students include the difficulty in identifying the main idea, implicit information, explicit information, referent, and word meaning in the text.Â The research data were collected by using techniques of observation, interview, field note, photographs, and test (pre-test and post-test). The quantitative and qualitative analyses show that mind mapping can improve both the studentsâ reading comprehension and the class situation. It can be seen by comparing the pre-test and the post-test score. Their mean score of pre-test, post-test 1, and post-test 2 were 57.99, 68.29, and 80.31.